Dental health dispositions of pregnant women: A survey from a hospital clinic in Istanbul. (18th August 2017) - Gokmen Karasu, Ayse Filiz; Kutuk, Nukhet; Aydin, Serdar; Adanir, Ilknur; Ates, Seda; Bademler, Neslihan
Abstract: Dental hygienic habits should be maintained in pregnancy despite challenges. We aimed to study the dental attitudes and habits of pregnant women. The patients attending our hospital clinic were invited to fill out a structured questionnaire categorised into three major domains: (1) general oral hygiene status, (2) dental habits, and (3) dental attandence both during pregnancy and prior to pregnancy. Four hundred and seventy four women agreed to participate. Mean age of participants was 28 (18–43). While 184 (38%) women reported brushing twice a day, only 98 (20%) women claimed using floss and or mouth rinse. Fifty-nine (12.4%) women had a dental visit in their current pregnancy and 24 (5.1%) received professional treatment. Obstetric care givers should convey the importance of dental care to their patients. We suggest that dental health should be improved antenatally, and be assessed in detail by dental health care providers. Impact Statement: Poor oral health conditions have shown to be associated with an increased risk of adverse pregnancy outcomes, especially in low-income countries and regions. There is escalating evidence to support the lack of awareness among pregnant women about health consequences and long term risks associated with poor oral hygiene. Our results showed that dental hygienic practices of pregnant women are disconcerting in Turkey. The need for inter-professional collaboration among obstetric healthcare providers and dental specialistis is crucial for conveying to women the importance of dental care in pregnancy and beyond.